UI/UX Design Of Mobile-Based Pharmacy Application Using Design Thinking Method - Suryani, Suryani; Nurdiansah, Nurdiansah; Faizal, Faizal; Nirwana, Nirwana; Johanis, Andrew Ridow; Marsa, Marsa; Pratama, Arkjun Yudistira (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
Pharmacy is a public facility that supplies, distributes, and serves medicine needs. Based on observations, Rania Farma Pharmacy is one of the pharmacies that still uses conventional methods of medicine management. The Pharmacist Assistant has to write down medicine stocks and transactions in a book, calculate sales with the help of a calculator, and monthly reporting by inputting daily sales in the Microsoft Office Excel application which takes quite a long time. This process is prone to human error, such as calculation and recording errors, which can harm pharmacies and consumers. This research uses the Design Thinking method to design a mobile-based pharmacy application based on the User Interface (UI) and User Experience (UX). Then perform prototype analysis using the System Usability Scale (SUS). Design Thinking includes software development methods focusing on solving human-centered problems. Pharmacy information needs are collected through observation, interviews, and literature study. In designing this information system, it is hoped that it can help medicine management at the Rania Farma Pharmacy. In testing the prototype, the analysis used is the System Usability Scale (SUS). The results of the SUS value were 79.5, which was included in the Good category. Therefore the design of the Pharmacy application can be used and developed to become a better and more useful system for pharmacies.